Development and validation of creatinine-based estimates of the Glo- Merular Filtration rate equation from Chromium Edta Imaging in the multi-racial Malaysian population - Wong, Chee Rong; Sharifuddin, Ina Ismiarti; Md Ralib, Azrina; Hui Chaw, Sook; Chan, Wai Yee; Dzaharudin, Fatimah; Lily, Nicetha; Ng WS, Kevin (Kugler Publication, 2022)
Background Glomerular filtration rate (GFR) is a reliable parameter for assessing kidney function. It is estimated from equations such as Cockcroft–Gault (CG), Modification of Diet in Renal Disease (MDRD), and Chronic Kidney Disease- Epidemiology Collaboration (CKD-EPI). However, these equations were derived using Western population demo- graphic data and had different performances when applied to other populations. Objectives. We developed a new equation (NE) based on the 51Cr EDTA measured GFR that can be used explicitly in the Malaysian multiracial population. Methods This was a cross-sectional study using the Electronic Medical Record (EMR) of pa- tients who underwent 51Cr-EDTA imaging at the Nuclear Medicine Centre, University Malaya Medical Centre (UMMC), from 2013 to 2021. This study had obtained approval from the Medical Research Ethics Committee, UMMC. Results Total data of 209 patients were recruited in this study. 105 were randomised in the development cohort, while 104 were in the validation cohort. A NE was developed based on data in the development cohort and then tested its performance in the validation cohort. The result showed that CKD-EPI had the highest correlation to 51Cr EDTA imaging measured GFR (r-value 0.82), followed by the NE (r-value 0.76). CG had the lowest bias (mean bias of 2.49), followed by the NE (mean bias of 3.52). CKD-EPI had the highest precision in estimating GFR (SD of 22.04ml/min), followed by the NE (SD of 25.05ml/min). CKD-EPI also had the highest accuracy (85.58% in P30 and 100% in P50, followed by MDRD (81.73% in P30 and 96.15% in P50). Conclusion The NE was less accurate than CKD-EPI and MDRD equation but generally has a rel- atively low bias of 3.52 ml/min. The limitation of the small sample size may limit the accuracy of the NE. Future studies with a larger sample size are needed to generate a more robust equation.